The Grotesque in Bergamo. J.P. Jacobsen’s Pesten i Bergamo in light of Bakhtin, Boccaccio, and Dante - Lee, Joshua (Folia Scandinavica Posnaniensia, 2024)
This article examines J.P. Jacobsen's short-story Pesten i Bergamo (1881) through the lens of Bakhtin's carnivalesque. Bakhtin's carnival is a medieval societal alterity which takes hold in times of societal upheaval, here the spread of plague, and is depicted in the medieval literary mode identified as grotesque realism. It notes the narrative points in Jacobsen's story that cohere to Bakhtin's grotesque realism in two ways: the debauchery of the Old Bergamese citizenry, and the carnivalesque mockery of medieval religious practices, providing a structured inversion of previous societal practices established in the short story. It also examines close intertextual links between these elements in Pesten i Bergamo and Giovanni Boccaccio's Decameron, offering a potential source for Jacobsen's usage of grotesque realism as a literary mode and his depiction of societal reactions to widespread illness. Finally, it explores the literary geography of Pesten i Bergamo and how it coheres to the verticality of Dante Alighieri's Commedia, specifically Inferno and Purgatorio. The article concludes that Jacobsen, knowingly or unknowingly, employed carnivalesque topoi to convey a medieval sense of medieval, following the medieval literary tradition broadly and more specifically the fourteenth-century Italian literary tradition, matching the temporal and geographic setting of Pesten i Bergamo.